Hubungan Penggunaan APD Terhadap Angka Kejadan Infeksi Nasokomial Pada Pasien Rawat Inap Di RSUD Alimuddin Umar Liwa Kabupaten Lampung Barat - Ismanto Nasim; Andoko Andoko; M. Arifki Zainaro (Universitas Malahayati Lampung, 2021)
ABSTRACT: RELATIONSHIP OF THE USE OF PPE TO THE INCIDENCE OF NOSOCOMIAL INFECTION IN INPATIENTS AT ALIMUDDIN HOSPITAL, UMAR LIWA, LAMPUNG BARAT DISTRICT Introduction: After conducting an in-depth survey, it was found that out of 53 medical personnel, it was found that 22 (41.5%) medical personnel did not comply with the use of PPE, and 31 (58.5%) medical personnel always complied. with the use of PPE.Purpose: The purpose of this study was to determine the relationship between the use of PPE with the prevalence rate of nosocomial infections in inpatients at Alimuddin Umar Liwa Hospital, West Lampung Regency in 2020.Methods: The type of research used in this research is quantitative with an analytic design, namely research that explores how and why health phenomena occur using a cross-sectional approach. The population in this study were all nurses at Alimuddin Umar Liwa Hospital, West Lampung Regency, totaling 96 people. The sample in this study amounted to 96 people. In this study, the sampling technique used was total sampling.Results: It is known that in the Alimuddin Umar Liwa Regional Hospital, West Lampung Regency in 2020, most of the respondents used bad PPE, namely 54 respondents (56.3%), and most of the respondents were at risk of experiencing nosocomial infections, amounting to 50 respondents (52.1%)Conclusion: Based on the results of statistical tests, the p-value is 0.000 or p-value 0.05, which means that there is a relationship between the use of PPE and the prevalence of nosocomial infections in hospitalized patients in the Alimuddin Umar Liwa area. West Lampung District Hospital 2020. The results of this study are expected. so that it becomes an input for Alimuddin Umar Hospital regarding the Relationship between the Use of PPE and the Occurrence of Nasocomial Infection in Inpatients so that with the use of good PPE it is hoped that the incidence of HAI can be resolved properly by giving warnings or even sanctions to nurses if they do not use PPE, as well as more supervision of nurses in using PPE. Keywords: Use of Personal Protective Equipment Incidence Rate of Nasocomial Infection INTISARI: HUBUNGAN PENGGUNAAN APD TERHADAP ANGKA KEJADAN INFEKSI NASOKOMIAL PADA PASIEN RAWAT INAP DI RSUD ALIMUDDIN UMAR LIWA KABUPATEN LAMPUNG BARAT Pendahuluan : Setelah dilakukan survey lebih dalam diketahui dari 53 tenaga medis, diketahui 22 (41,5%) tenaga medis tidak patuh terhadap penggunaan APD, dan 31 (58,5%) tenaga medis selalu patuh dengan penggunaan APD.Tujuan: tujuan dalam penelitian ini adalah Diketahui Hubungan Penggunaan APD Terhadap Angka Kejadan Infeksi Nasokomial Pada Pasien Rawat Inap Di RSUD Alimuddin Umar Liwa Kabupaten Lampung Barat Tahun 2020.Metode : Jenis penelitian yang digunakan dalam penelitian ini adalah kuantitatif dengan rancangan analitik yang artinya penelitian yang menggali bagaimana dan mengapa fenomena kesehatan itu terjadi, dengan menggunakan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh perawat pelaksanaan Di RSUD Alimuddin Umar Liwa Kabupaten Lampung Barat yang berjumlah 96 orang. Sampel dalam penelitian ini berjumlah 96 orang. Dalam penelitian ini teknik sampling yang digunakan adalah Total Sampling. Hasil : Diketahui bahwa Di RSUD Alimuddin Umar Liwa Kabupaten Lampung Barat Tahun 2020, sebagian besar responden menggunakan APD kurang baik yang berjumlah 54 responden (56,3%) dan sebagian besar responden berisiko mengalami infeksi nasokomial yang berjumlah 50 responden (52,1%)Kesimpulan : Berdasarkan hasil uji statistik, didapatkan p-value 0,000 atau p-value 0,05 yang artinya terdapat Hubungan Penggunaan APD Terhadap Angka Kejadan Infeksi Nasokomial Pada Pasien Rawat Inap Di RSUD Alimuddin Umar Liwa Kabupaten Lampung Barat Tahun 2020. Hasil penelitian ini diharapkan agar menjadi bahan masukan bagi RSUD Alimuddin Umar tentang Hubungan Penggunaan APD Terhadap Angka Kejadan Infeksi Nasokomial Pada Pasien Rawat Inap, sehingga dengan penggunaan APD yang baik diharapkan angka kejadian HAIs dapat di atasi dengan baik dengan cara memberikan peringatan atau bahkan sanksi kepada perawat jika tidak menggunakan APD, serta lebih melakukan pengawasan terhadap perawat dalam penggunaan APD. Kata Kunci: Penggunaan Alat Pelindung Diri Angka Kejadian Infeksi Nasokomial